Biochemical, physicochemical property and archaea community characteristics in casing soil of cultivating Stropharia rugosoannulata - Liu, Jinjia; Wang, Xiang; Su, Wenting; Wang, Jixiang; Wu, Jinqiang; Tian, Songhao (Frontiers in Microbiology, 2025)
Mulching is very important in the cultivation of Stropharia rugosoannulata and helps in the formation of edible mushroom substrates. The physicochemical properties of soil are crucial for the growth process of edible mushroom substrates. In this study, we evaluated the enzyme activities, physicochemical properties, nutrient indicators, and archaeal community characteristics of soil during five stages of cultivation of Stropharia rugosoannulata (casing, mycelial, primordial, growing, and harvesting). The results showed that sucrase activity decreased significantly and then increased with the increase of cultivation time, and urease activity fluctuated and then decreased significantly. Catalase activity peaked at stage A5. Polyphenol oxidase activity was significantly higher at stage A2 and lowest at stage A4. Soil pH reached its lowest (7.130) at stage A5 after fluctuation. Soil total organic matter content was highest at stage A5 and reached maximum at stage A5 (8.357 g/kg). Organic nitrogen content was for was significantly higher in A4 stage at 0.276 g/kg. Organic content was significantly higher in A1 and A4 stages (0.401, 0.397 g/kg). The number and diversity of archaea in the soil gradually increased, and a total of 10 genera of archaea from six phyla were identified. The present study provides data on soil characteristics and archaeal communities in the overburden of Stropharia rugosoannulata at different stages of cultivation, which can contribute to the sustainable cultivation of Stropharia rugosoannulata and the reduction of live pollutants.